El bien público defensa en el siglo XXI: una mirada al gasto de defensa regional - Palomino Milla, Fernando (Hemisferio - Revista del Colegio Interamericano de Defensa, 2019)
Defense expenditures and economic issues related to the defense sector, in general, are rarely researched and discussed within civil society. Given that national defense is a public good that is intangible and cross-cutting it must compete with others sectors for funding its public policies and in the context of opportunity costs submit to political, academic scrutiny, as well as by civil society. This paper is intended to provide a critical reflection on the significant role of defense expenditures in the region and explore the expenditures measurement processes required for funding this public good including the most recent generation of confidence and security building measures.